Working Dog Service, Harmful Agent Exposure and Decontamination - Jarrett, Carla L.; Brathwaite, Morgan; Gogal, Robert M.; Holladay, Steven D. (Frontiers in Veterinary Science, 2022)
Working dogs are widely used by service professionals and the military for diverse roles that include sentry, patrol, messenger, tracking, search and rescue, law enforcement, apprehension, as well as explosives and narcotics detection. The expected tasks performed are in many ways determined by the breed, which is customarily a German Shepherd, Dutch Shepherd, Golden Retriever, Border Collie, Labrador Retriever, Beagle, or Belgium Malinois. Working dogs may be subject to injury from dangerous work environments or harmful agent exposure. Personal protective equipment (PPE) has been developed for such dogs, but may impede performance of duties or be poorly tolerated. Canine-specific field-use ready decontamination techniques and kits are therefore needed for use on working dogs that have encountered a harmful agent exposure. This report briefly reviews the development of the military working dog and examines personal protective equipment and decontamination techniques for working dogs after exposure to harmful biologic or chemical agents.